A New Species of Platythyrea (Hymenoptera; Formicidae) From Costa Rica - Charies Kugler (Psyche: A Journal of Entomology)
A new species of Platythyrea was found in the Field Museum insect collections too late to be included in Brown’s (1975) revision of the genus. Eleven workers were collected by Dr. John Wagner and Dr. John Kethley from beflesates at the La Selva Field Station of the Organization for Tropical Studies in Costa Rica. A formal description is offered herewith. Measurements are as defined in Brown (1975:3).